ANALISIS KINERJA KEUANGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED PADA BANK SUMUT SYARIAH KANTOR CABANG PEMBANTU H.M. YAMIN MEDAN - Ningrum, Azizah Sekar; Imsar, Imsar; Syafina, Laylan (LPPM - STIE SAKTI ALAM KERINCI, 2024)
This research is a quantitative study that analyzes financial performance in using the Economic Value Added method at Bank Sumut Syariah Sub-Branch H.M Yamin Medan in the 2018-2022 period. To analyze the financial performance of Bank Sumut Syariah Sub-Branch H.M Yamin Medan from year to year before and after the economic shock period by covid 19. This type of research is descriptive quantitative research. The population of this research is Sharia Business Units in Indonesia, the sample used for this research is the financial statements of Bank Sumut Syariah Sub-Branch H.M Yamin Medan in 2018-2022. This research analysis was conducted because it wanted to describe financial performance and wanted to see how much added value could be generated, so researchers used the Economic Value Added (EVA) approach in determining added value. The results showed a fluctuating movement in EVA value on the financial performance of Bank Sumut Syariah Sub-Branch H.M Yamin Medan in the period 2018-2022. In the year the decline in financial performance only occurred in 2020 where the covid 19 outbreak was sweeping Indonesia.